2007
DOI: 10.1537/ase.061219
|View full text |Cite
|
Sign up to set email alerts
|

Metric dental diversity of Ryukyu Islanders: a comparative study among Ryukyu and other Asian populations

Abstract: Mesiodistal and buccolingual crown diameters were examined to describe and compare patterns of metric dental variation in five modern samples from the Ryukyu Island chain (Miyako, Ishigaki, Tokunoshima, and two samples from Okinawa Island). Principal component analysis applied to two separate datasets, raw measurement and standardized (C-score) data, for 32 Asian and Pacific samples, including the five Ryukyu Islander series, produced an overall size factor and three shape factors (relative size of mesiodistal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 60 publications
0
21
1
1
Order By: Relevance
“…The Ryukyu Islanders were also considered probable descendants of the Jomon people according to the "dualstructure model"; however, successive Japanese migration and/or genetic contribution from the south probably contributed to phenotypic changes leading to the recent Ryukyu Islanders (Hatta et al, 1999;Fukumine et al, 2006). Because of the northeastern continental scope of the present study, no comparative samples from southeastern Asia were included so that hypotheses of genetic contribution to the Ryukyu Islanders could not be specified; however, the greater phenotypic variance seen in the Ryukyu Islanders in this study (Table 2) and other studies Toma et al, 2007;Komesu et al, 2008) supports a possible external genetic contribution in the Ryukyu Islanders.…”
Section: Okhotsk Ainu and Ryukyu Peoplesmentioning
confidence: 73%
See 1 more Smart Citation
“…The Ryukyu Islanders were also considered probable descendants of the Jomon people according to the "dualstructure model"; however, successive Japanese migration and/or genetic contribution from the south probably contributed to phenotypic changes leading to the recent Ryukyu Islanders (Hatta et al, 1999;Fukumine et al, 2006). Because of the northeastern continental scope of the present study, no comparative samples from southeastern Asia were included so that hypotheses of genetic contribution to the Ryukyu Islanders could not be specified; however, the greater phenotypic variance seen in the Ryukyu Islanders in this study (Table 2) and other studies Toma et al, 2007;Komesu et al, 2008) supports a possible external genetic contribution in the Ryukyu Islanders.…”
Section: Okhotsk Ainu and Ryukyu Peoplesmentioning
confidence: 73%
“…The Yayoi immigrants showed clear modern East Asian features (Nakahashi and Li, 2002). Although the basic approach of this model is quite valid, the dual-structure hypothesis is too simple to explain the population history for all of the Japan Islands Toma et al, 2007); in particular, after the Yayoi immigration to the Japanese main islands, the people of the Okhotsk culture came from northeastern Asia to the Sakhalin and Hokkaido Islands during the 5th-12th centuries AD (Kikuchi, 1999;Amano, 2003). Archeological evidence and isotopic analysis show that the Okhotsk culture had developed a considerable maritime infrastructure (Yoneda, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…We also used specimens from 73 individuals from the Sakishima Islands, the western islands of Okinawa, that had also participated in previous studies (Japanese set 3). 14,34,35 All the subjects gave informed consent for their participation in this study. This study was conducted with the approval of ethical committees of the Showa University, the Pusan National University and the University of the Ryukyus.…”
Section: Study Subjectsmentioning
confidence: 99%
“…The craniofacial morphology of ancient and modern people in the Japanese archipelago has been well studied (von Baelz, 1911;Ikeda, 1974;Brace and Nagai, 1982;Hanihara, 1991;Ishida, 1992;Pietrusewsky, 1999;Dodo et al, 2000;Higa et al, 2003;Fukumine et al, 2006;Haneji et al, 2007;Toma et al, 2007;Fukase et al, 2012;Miyazato et al, 2014). Such studies have revealed that craniofacial features, including dental characteristics, show regional differences even within Japan, especially between the mainland Japanese, Ryukyu Islanders, and Ainu.…”
Section: Introductionmentioning
confidence: 99%